An analysis of the extent to which companies in the oil industry are environmentally responsible - Wheelhouse, Luke James (2009)
Behind pessimistic expectations regarding the future of an international climate treaty, substantial changes can be observed in company positions. Multinationals in the oil industry are increasingly moving towards support for the Kyoto Protocol, and have taken measures to address climate change.